(untitled) (Malaysian Management Journal, 2019)
Social marketing is the art of marketing for the society. With the present environment confronted with numerous issues related to society and health, social marketing can be used as a humble way to address them. This study explores the scope of social marketing in de-marketing smoking habits. Consequently, it unveils the perception of consumers on the issue of smoking, and examine how people react on seeing a form of de-marketing advertisement on the cigarette packet. Finally, this paper provides suggestions for campaigns through social marketing to address the issue. This study is exploratory and descriptive in nature, involving a sample of 400 respondents. Factor analysis has been administered in analysing the data. This study reveals that people smoke due to addiction and out of the desire to socialize. Further, a section of smokers view smoking as having the capacity to relieve a person from depression. As far as seeing the de-marketing advertisement is concerned, smokers have a tendency to go for emotional forgetting as they simply ignore the statutory warning. These are vital input for social marketers to formulate policies. Social marketers involved in de-marketing campaigns can highlight that a person can achieve status in a society by virtue of exploiting one’s own innovative skills and talents. Further positive contribution to the society gives one an eternal pleasure in life. Lastly marketers can pinpoint that regular exercise, good sleep, healthy diet and positive thinking can relieve oneself from stress.